Trust your eyes [large type] : a thriller - Barclay, Linwood (Thorndike Press, 2012)
Thomas Kilbride is a map-obsessed schizophrenic who rarely leaves the bastion of his bedroom. But with a computer program called Whirl360.com, he travels the globe. Memorizing the streets of the world, Thomas examines every address as well as the people frozen in time on his computer screen. Then he sees something that anyone else could have, but didn't: an image in a window that looks like a woman being murdered.